ANALISIS REDUKSI DIMENSI PADA KLASIFIKASI MICROARRAY MENGGUNAKAN MBP POWELL BEALE - MUNZIR, ANDI FUTRI HAFSAH; ADIWIJAYA, ,; ADITSANIA, ANNISA (E-Jurnal Matematika, 2018)
Cancer is the second leading cause of death in the world based on World Health Organization (WHO) survey in 2015. It took DNA microarray technology to analyze and diagnose cancer. DNA microarray has large dimensions so it influences the process of cancer ‘s classification. GA and PCA are used as reduction method and MBP Powell Beale as classification method. The testing of MBP classification without dimension reduction results 70, 59% ? 100% accuracy. MBP+PCA results 76, 47% ? 100% accuracy. MBP + GA results 76, 47% ? 92, 31% accuracy.